Rheumatoid arthritis-like features in Hansen disease: A case report. Issue 29 (July 2018) - Gao, Le-Nyu; Zhong, Bing; Wang, Yong
Abstract: Rationale: Hansen disease is an infectious chronic disease with various clinical manifestations. Its joint performance may easily mimic rheumatoid arthritis. Patient concerns: We report a case of a 57-year-old woman diagnosed with Hansen disease 10 years ago, who suffered from joints swelling, pain and joints deformities of both hands for 19 years. The skin on the hands showed rashes, thickening, desquamation and chapping, with both thenar muscles atrophy. She also had severe hypoalgesia of the whole body, and morning stiffness for one hour. Diagnoses: The final diagnosis was joint damage and peripheral neuropathy due to Hansen disease. Interventions: The patient received neurotrophic treatment instead of anti-rheumatic treatment. Outcomes: At 1-year follow up, no further aggravation of joint swelling and pain was detected. Lessons: The correct diagnosis of Hansen disease involving joints depends on the combination of medical history, careful physical examination, and laboratory examination.